2022
DOI: 10.3389/fpubh.2022.963138
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary metals and leukocyte telomere length involving an artificial neural network prediction: Findings based on NHANES 1999–2002

Abstract: ObjectiveLeukocytes telomere length (LTL) was reported to be associated with cellular aging and aging related disease. Urine metal also might accelerate the development of aging related disease. We aimed to analyze the association between LTL and urinary metals.MethodsIn this research, we screened all cycles of National Health and Nutrition Examination Survey (NHANES) dataset, and download the eligible dataset in NHANES 1999–2002 containing demographic, disease history, eight urine metal, and LTL. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Almost all cells in human body can synthesize TGF-β 1, which has the functions of immune regulation, promoting cell growth and differentiation, angiogenesis, immune regulation and so on ( Desai et al, 2018 ). Some studies ( Narod et al, 2015 ; Zheng et al, 2020 ; Chandra Jena et al, 2021 ; Xia et al, 2022 ) have found that under normal physiological conditions, TGF- β 1 inhibits the growth of tumor cells, and this inhibition still exists in the early stage of tumor, but once tumor cells enter the uncontrollable growth stage, the inhibition of TGF- β 1 will turn into promoting effect, leading to tumor occurrence and development. At present, related studies ( Zhang et al, 2014 , 7; Labrèche et al, 2021 ) have corroborated that BC-associated fibroblasts (CAFs) and epithelial-mesenchymal transformation (EMT) are the key links of tumor cell proliferation and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all cells in human body can synthesize TGF-β 1, which has the functions of immune regulation, promoting cell growth and differentiation, angiogenesis, immune regulation and so on ( Desai et al, 2018 ). Some studies ( Narod et al, 2015 ; Zheng et al, 2020 ; Chandra Jena et al, 2021 ; Xia et al, 2022 ) have found that under normal physiological conditions, TGF- β 1 inhibits the growth of tumor cells, and this inhibition still exists in the early stage of tumor, but once tumor cells enter the uncontrollable growth stage, the inhibition of TGF- β 1 will turn into promoting effect, leading to tumor occurrence and development. At present, related studies ( Zhang et al, 2014 , 7; Labrèche et al, 2021 ) have corroborated that BC-associated fibroblasts (CAFs) and epithelial-mesenchymal transformation (EMT) are the key links of tumor cell proliferation and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no definite conclusion on the correlation between the LTI angle and the patellar cartilage injury. Stefanik and other researchers have asserted that the LTI angle is significantly related to the patellar cartilage injury, but this is just opposite to the conclusion of previous reports (29)(30)(31)(32)(33)(34). In this study, the LTI angle of the control group was significantly greater than that of the CP group, which was consistent with Stefanik's conclusion.…”
Section: Discussioncontrasting
confidence: 59%
“…Data was derived from the six continuous NHANES cycles from 2007-2008 to 2017-2018, which is a nationally representative population-based survey for assessing adult and child health and nutritional status in the United States [ 21 ]. The examination components consisted of medical, dental, and physiological measurements, and laboratory tests, which were supervised by trained medical personnel.…”
Section: Methodsmentioning
confidence: 99%